Edukasi Penanganan Nonfarmakologi Nyeri Otot Kronis - Margo, Eveline; Kartadinata, Erlani; Meiyanti; Yohana; Murthi, Aditya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Chronic pain can result from various clinical conditions and may persist for more than three months. The symptoms can range from mild to severe. While chronic pain can be associated with various diseases, its exact cause sometimes remains unclear. In 2019, data from the National Health Interview Survey in the United States indicated that approximately 1 in 5 adults experienced chronic pain, with over 7% frequently limiting their activities due to this condition. However, there is no comparable data available for Indonesia. Chronic pain restricts activities and can decrease a person’s quality of life. Various options are available for pain management, one of which is non-pharmacological therapy, including hot-cold compresses, massage and stretching techniques, music therapy, and aromatherapy. These therapies aim to improve bodily function, regulate emotions, reduce weakness, stress, and anxiety, and decrease the need for pain medication. Gout is among the most common causes of chronic pain, with a prevalence of 3.9% in the US, 2.5% in Europe, and 7.3% in Indonesia, according to Riskesdas (2018). Based on this, local citizens were provided with education about pain management. This community service activity involved educating citizens on non-pharmacological treatments for chronic pain management and offering health services to residents of Angke. The purpose was to increase knowledge about non-pharmacological treatments for managing chronic pain. This activity was conducted on April 27th, 2024, from 07.00 to 12.00 at the Dhammasavana School in the Angke sub-district area, West Jakarta. The activities proceeded smoothly and in an orderly manner. A comparison of citizens’ knowledge before and after the education revealed a 58.18% increase in knowledge, contributing to improved welfare among the local residents.